Benefits of incorporating Dy–Cu alloy via the grain boundary diffusion process in recycled magnets - M.B.S. Dias; G.Y.S. Shimizu; L.L. Azevedo; D.L. Rodrigues-Jr; W.C. Macedo; L.F. Antunes; L.U. Lopes; P.A.P. Wendhausen; R.N. Faria; C.A.L. Santos; F.A.C. Pastrián; F.J.G. Landgraf (Journal of Materials Research and Technology)
Nd-Fe-B magnets are a critical material for the green energy transition. However, price volatility makes the supply chain fragile, which makes the recycling process an alternative to reduce dependence on raw materials. Unfortunately, the recycling process introduces oxygen into the magnet, getting worse magnetic properties. Thus, this article studies the effects of the grain boundary diffusion (GBD) process with Dy–Cu slurry on the magnetic and corrosion properties of recycled magnets. As expected, the recycling process reduced the coercivity from 1350 kA/m to 850 kA/m and also decreased the coercivity thermal stability (β) from −0,530 %/°C to of −0.590 %/°C. The introduction of oxygen reduces the amount of the Nd-rich phase, preventing the formation of a grain boundary phase. However, since Nd oxides are more electrochemically stable than the Nd-rich phase, an improvement in corrosion resistance occurred. Regarding the GBD performed at 900 °C increases the coercivity to 1290 kA/m and achieves higher thermal stability (β = −0.54 %/°C) compared to recycled magnets. During GBD, a Dy-rich shell composed of (Dy + Nd + Pr)2Fe14B was formed around the Φ phase grains. Since Dy locally increases the magnetic anisotropy on the surface of the Φ phase grains, a higher magnetic field is required to nucleate an opposite magnetic domain. Moreover, the recycled magnet treated with GBD at 900 °C exhibits higher corrosion resistance than End-of-Life magnets. In summary, the GBD could be an alternative to partially recover the coercivity of recycled magnets, resulting in a magnet with higher corrosion resistance than End-of-Life magnets.